Fermented barley β‐glucan regulates fat deposition in Caenorhabditis elegans. (7th April 2020) - Xiao, Xiang; Tan, Cui; Sun, Xinjuan; Zhao, Yansheng; Zhang, Jiayan; Zhu, Ying; Bai, Juan; Dong, Ying; Zhou, Xinghua
Abstract: BACKGROUND: Barley contains a relatively high concentration of the mixed‐linkage (1 → 3) (1 → 4) β ‐glucan, which has been reported to be a functional food with prebiotic potential. In the current study we compared the properties of two neutral barley β ‐glucans, obtained from raw barley: raw barley β ‐glucan (RBG) and Lactobacillus plantarum dy‐1‐fermented barley (FBG). RESULTS: Molecular characteristics revealed that the molecular weight of barley β ‐glucan decreased from 1.13 × 10 5 D to 6.35 × 10 4 D after fermentation. Fermentation also improved the water / oil holding capacity, solubility, and swelling capacity of barley β ‐glucan. Both RBG and FBG significantly improved the locomotive behavior of nematodes, thereby increasing their energy consumption and reducing fat deposition – the effect was more significant with FBG. These effects could potentially depend on nhr‐49, TGF‐ daf‐7 mediated pathways and so on, in which nhr‐49 factor is particularly required. CONCLUSION: These results suggested that fermentation may enhance in vitro physiological activities of barley β ‐glucan, thereby altering the effects on the lipid metabolism in vivo . © 2020 Society of Chemical Industry